ANALISIS TEMPERATUR ANALISIS TEMPERATUR LINGKUNGAN TERHADAP KINERJA COOLING TOWER TIPE INDUCED DRAFT UNIT 2 - Harwan Ahyadi (Institut Sains dan Teknologi Nasional, 2020)
Cooling tower is very necessary in every industry, especially in the geothermal power plant industry in the framework of implementation for efficiency and energy conversion where a tool or unit is used for circulation of cooling water. The function of the cooling tower is to process hot water into cold water, so that it can be used again. In the cooling tower specification data, the range value is 16.7 ° C, with an approach of 6.5 ° C, and with an efficiency of 71.98%. The results of the calculation of the analysis obtained a range value of 22.3 ° C, with an approach of 6.3 ° C, and with an efficiency of 77.97%. From the results of the analysis, the range, approach, and efficiency values were increased by 5.92% compared to the cooling tower specification data. Keywords: Cooling Tower, Inducted Draft, Range, Approach, Efficiency